A survey on network forwarding in Software-Defined Networking. (15th February 2021) - Yang, Liang; Ng, Bryan; Seah, Winston K.G.; Groves, Lindsay; Singh, Deepak
Abstract: The packet forwarding behaviour of a network relies on the forwarding rules residing in the networking element (e.g. switches and routers) to forward packets. This applies to both traditional networking and software-defined networking (SDN). These forwarding rules vary in their structures and sizes, but they represent the same fundamental functionality: to match incoming packets against rules and determine its forwarding behaviour. All these rules in a network device constitute a packet forwarding pipeline. This survey paper presents a new taxonomy for the representation of the forwarding pipeline in SDN based on core networking functionality. The new taxonomy uses a typology and attributes of the forwarding behaviour to establish a cohesive vocabulary and a classification system to study and characterise the interactions of FTE along an end-to-end path in SDN. The survey also shows that Boolean algebra is most widely used for the low-level representation of FTEs and facilitates the assessment of "equivalence" between FTEs and has practical uses in traffic monitoring and packet classification within SDN, among others. Highlights: Packet forwarding pipeline in traditional network includes ACL and IP routing entry. In SDN, forwarding pipeline includes generic type of forwarding table entry (FTE). A thorough review on representations for the packet forwarding pipeline. FTE has manifested as a generic form of ACL and IP routing entry in SDN. The Boolean Algebra is best suitable for the low-level representations of FTEs.